1974
DOI: 10.1042/bj1390109
|View full text |Cite
|
Sign up to set email alerts
|

The kinetic mechanism and properties of the cytoplasmic acetoacetyl-coenzyme A thiolase from rat liver

Abstract: 1. Cytoplasmic acetoacetyl-CoA thiolase was highly purified in good yield from rat liver extracts. 2. Mg(2+) inhibits the rate of acetoacetyl-CoA thiolysis but not the rate of synthesis of acetoacetyl-CoA. Measurement of the velocity of thiolysis at varying Mg(2+) but fixed acetoacetyl-CoA concentrations gave evidence that the keto form of acetoacetyl-CoA is the true substrate. 3. Linear reciprocal plots of velocity of acetoacetyl-CoA synthesis against acetyl-CoA concentration in the presence or absence of des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

1975
1975
2002
2002

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 22 publications
4
69
0
Order By: Relevance
“…They are rather a consequence of a competition bctween acetoacetyl-CoA and CoA for the free form of enzyme A and B. CoA reacts both as substrate in the normal reaction sequence and with the free enzyme. Similar results are also obtained in studies with the cytoplasmic acetoacetyl-CoA thiolase [12].…”
Section: Kinetic Properties Qf Acetoacetyl-coa Thiolasrs a And B Iri supporting
confidence: 76%
See 1 more Smart Citation
“…They are rather a consequence of a competition bctween acetoacetyl-CoA and CoA for the free form of enzyme A and B. CoA reacts both as substrate in the normal reaction sequence and with the free enzyme. Similar results are also obtained in studies with the cytoplasmic acetoacetyl-CoA thiolase [12].…”
Section: Kinetic Properties Qf Acetoacetyl-coa Thiolasrs a And B Iri supporting
confidence: 76%
“…10 and 11) are consistent with the formation of a stable enzyme form F according to Cleland's notation [13] and exclude a sequential mechanism. This stable form is identical with acetyl-S-enzyme as already demonstrated for pig heart acetoacetyl-CoA thiolase and the cytoplasmic acetoacetyl-CoA thiolase from rat liver [21,12]. If there are reversible connections between the points of combination of acetyl-CoA, reciprocal plots of initial velocities versus substrate concentrations should become parabolic [13].…”
Section: Kinetic Properties Qf Acetoacetyl-coa Thiolasrs a And B Iri mentioning
confidence: 99%
“…The kinetic experiments were exclusively performed with transferase B, first with potassium, an activator [31], and then with sodium present. This enzyme form is not modified by bound CoASH, shows in vitro no charge heterogeneity, exhibits the higher specific activity and therefore has to be looked upon as the more active, native acetyl-CoA acetyltransferase [34].…”
Section: Resultsmentioning
confidence: 99%
“…Asterisks indicate the occurrence of substrate inhibition. reported before by others for cTh [1,3]. These similarities in chromatographic behaviour as well as the low activity of pTh in whole peroxisomes in comparison to the activities of the known peroxisomal thiolases suggested that we might have purified a contaminant cytosolic acetoacetyl-CoA thiolase from the peroxisomal fraction.…”
Section: Comparison Of the Properties Of The Acetoacetyl-coa Thiolasementioning
confidence: 72%